Secondary battery, positive electrode active material, preparation method of positive electrode active material and electric device

By doping silicon and element A in the high-nickel positive electrode material to form high-entropy doping, the problems of decreasing thermal stability and shortening of cycle life of the high-nickel positive electrode material are solved, and better cycle performance and capacity maintenance are achieved.

CN119852539APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411139985.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In applications, high-nickel positive electrode materials have performance problems caused by reduced thermal stability, reduced cycle life and reaction with air.

Method used

Doping silicon (Si) and elements A (such as Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti, La) in the positive electrode active material of the secondary battery improves cycling performance and reduces capacity reduction by forming high entropy doping.

Benefits of technology

The cycling performance of the secondary battery is improved, while the capacity reduction amplitude of the positive electrode material is reduced, achieving better electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852539A_ABST
    Figure CN119852539A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a secondary battery, a positive electrode active material, a preparation method of the positive electrode active material and a power utilization device. The secondary battery comprises an outer package, an electrode assembly and an electrolyte, the electrode assembly comprises a positive pole piece, a negative pole piece and an isolating membrane, the positive pole piece comprises a positive active material, and the positive active material comprises a compound shown in the formula 1 and a doping element: Li < 1 + a > Ni < x > M < 1-x > O < 2 >, a < lt >; 0, 0.08, 0.8 lt; xlt; m comprises at least one of Co, Mn and Al; the doping elements comprise Si and an element A, the element A comprises at least one of Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti and La, and the Si and the element A are doped in the bulk phase of the compound shown in the formula 1. Si and the element A are doped in the positive electrode active material at the same time, the cycle performance can be improved, and meanwhile the capacity reduction amplitude is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and particularly to secondary batteries, positive active materials, methods for preparing the same, and electrical devices using the same. Background Art

[0002] High-nickel cathode materials have been widely used in lithium-ion batteries due to their high energy density. However, high-nickel cathode materials are more reactive, which also brings many new challenges in applications, such as (1) with the increase of nickel content, the thermal stability of the material decreases; (2) the cycle life decreases; (3) during the preparation and storage processes, it is easier to react with water and CO 2 in the air to produce LiOH and Li 2 CO 3 , further affecting the viscosity and coating performance of the positive electrode slurry.

[0003] Therefore, the current technologies related to high-nickel cathode materials still need to be improved. Summary of the Invention

[0004] In order to solve the above problems at least to a certain extent, the present application provides a secondary battery. The positive active material in the secondary battery is doped with Si and element A at the same time, which can effectively improve the cycle performance of the secondary battery while reducing the capacity reduction rate of the positive active material.

[0005] In one aspect of the present application, the present application provides a secondary battery. According to an embodiment of the present application, the secondary battery includes an outer package and an electrode assembly and an electrolyte located inside the outer package. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is located between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive active material, and the positive active material includes a compound shown in Formula 1 and a doping element:

[0006] Li 1+a Ni x M 1-x O 2 Formula 1

[0007] wherein, 0 < a < 0.08, 0.8 < x < 1.0, and M includes at least one of Co, Mn, and Al;

[0008] The doping element includes Si and element A, and element A includes at least one of Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti, and La.

[0009] In the secondary battery according to the embodiment of the present application, the simultaneous doping of Si and element A in the positive active material forms high-entropy doping in the bulk phase, which can improve the cycle performance of the secondary battery while reducing the capacity reduction rate of the positive electrode material.

[0010] According to the embodiment of the present application, the Si is uniformly distributed in the compound represented by Formula 1. Thus, the Si element is beneficial to effectively play a role in improving the cycle performance of the secondary battery.

[0011] According to an embodiment of the present application, the element A is uniformly distributed in the compound represented by Formula 1.

[0012] Specifically, during the preparation process, the compound of Si and element A can undergo a low eutectic phenomenon to form a molten salt system, which helps Si and element A to be doped into the bulk phase of the positive electrode active material and evenly distributed, thereby better playing a role in improving cycle performance and alleviating capacity reduction.

[0013] According to the embodiments of the present application, the average doping concentration of Si in the compound represented by Formula 1 is 1000 ppm to 10000 ppm, calculated by mass ratio. Within the above doping concentration range, the cycle performance of the positive electrode active material can be well improved.

[0014] According to the embodiment of the present application, the average doping concentration of the element A in the compound represented by the formula 1 is 1000ppm to 10000ppm, calculated by mass ratio. Within the above doping concentration range, the reduction in the capacity of the positive electrode active material caused by doping Si can be effectively alleviated.

[0015] According to an embodiment of the present application, the doping element further includes element D, and the element D includes at least one of Mo, Ta, W, Sb, Sn and Nb. Specifically, element D can inhibit grain coarsening, widen the sintering range, help to obtain better crystallinity, release stress during the cycle process, slow down the formation of microcracks, and thus improve the cycle performance of the secondary battery.

[0016] According to the embodiments of the present application, the doping concentration of the element D at the grain boundary is greater than the doping concentration inside the grain. Specifically, the element D segregates and enriches at the grain boundary, which can further inhibit grain coarsening, widen the sintering range, obtain better crystallinity, increase the material porosity, and facilitate stress release and slow down microcrack formation during the cycle. In addition, it can be used as a Li lithium conductor to increase capacity; and as a grain boundary layer coating, it can effectively inhibit electrolyte side reactions and improve the cycle performance of secondary batteries.

[0017] According to the embodiments of the present application, the average doping concentration of the element D in the compound represented by the formula 1 is 500ppm to 5000ppm, calculated by mass ratio. Within the above doping concentration range, the effects of grain refinement, widening sintering temperature, and slowing down microcrack formation are further improved.

[0018] According to an embodiment of the present application, the Li / Ni mixing degree of the positive electrode active material is 2.5% to 6%. Within the above Li / Ni mixing degree range, high-entropy doping can be achieved to stabilize the crystal lattice, and at the same time, the Li / Ni mixing degree is relatively low, which is beneficial to improving the electrochemical properties such as the capacity and cycle performance of the secondary battery.

[0019] In the second aspect of the present application, a positive electrode active material is provided. According to an embodiment of the present application, the positive electrode active material includes a compound represented by Formula 1 and a doping element:

[0020] Li 1+a Ni x M 1-x O 2 Formula 1

[0021] wherein, 0 < a < 0.08, 0.8 < x < 1.0, and M includes at least one of Co, Mn, and Al;

[0022] The doping element includes Si and element A, and the element A includes at least one of Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti, and La.

[0023] In this positive electrode active material, doping Si can improve the cycle performance of the secondary battery using this positive electrode active material. At the same time, doping element A can reduce the amplitude of capacity reduction caused by doping Si. The secondary battery using this positive electrode active material has good cycle performance while taking into account a relatively high capacity.

[0024] According to an embodiment of the present application, the element A includes at least one of Sr, B, and Al. Thus, Si is more easily doped into the bulk phase of the compound represented by Formula 1, the structural stability can be further improved, and at the same time, the amplitude of capacity reduction of the positive electrode active material is relatively small.

[0025] According to an embodiment of the present application, the Si is uniformly distributed in the compound represented by Formula 1. Thus, it is beneficial for the Si element to effectively play the role of improving the cycle performance of the secondary battery.

[0026] According to an embodiment of the present application, the element A is uniformly distributed in the compound represented by Formula 1. Specifically, during the preparation process, the compounds of Si and element A can undergo a eutectic phenomenon to form a molten salt system, which helps Si and element A to be doped into the bulk phase of the positive electrode active material and be uniformly distributed, thereby better playing the role of improving the cycle performance and alleviating the capacity reduction.

[0027] According to an embodiment of the present application, calculated by mass ratio, the average doping concentration of Si in the compound represented by Formula 1 is 1000 ppm to 10000 ppm. Within the above doping concentration range, the cycle performance of the positive electrode active material can be well improved.

[0028] According to the embodiments of the present application, the average doping concentration of the element A in the compound represented by the formula 1 is 1000ppm to 10000ppm, calculated by mass ratio. Within the above doping concentration range, the capacity reduction caused by doping with Si element can be effectively alleviated.

[0029] According to an embodiment of the present application, the doping element further includes element D, and the element D includes at least one of Mo, Ta, W, Sb, Sn and Nb. In some specific examples, element D includes W. Specifically, element D can inhibit grain coarsening, widen the sintering range, help to obtain better crystallinity, release stress during the cycle process, slow down the formation of microcracks, and thus improve the cycle performance of the secondary battery.

[0030] According to the embodiments of the present application, the doping concentration of the element D at the grain boundary is greater than the doping concentration inside the grain. Specifically, the element D segregates and enriches at the grain boundary, which can further inhibit grain coarsening, widen the sintering range, obtain better crystallinity, increase the material porosity, and facilitate stress release and slow down microcrack formation during the cycle. In addition, it can be used as a Li lithium conductor to increase capacity; and as a grain boundary layer coating, it can effectively inhibit electrolyte side reactions and improve the cycle performance of secondary batteries.

[0031] According to the embodiments of the present application, the average doping concentration of the element D in the compound represented by Formula 1 is 500ppm to 5000ppm, calculated by mass ratio. Within the above doping concentration range, the effects of grain refinement, widening sintering temperature, and slowing down microcrack formation are further improved.

[0032] According to the embodiment of the present application, the Li / Ni mixing degree of the positive electrode active material is 2.5% to 6%. Within the above Li / Ni mixing degree range, high entropy doping can be achieved to stabilize the lattice, while the Li / Ni mixing degree is relatively low, which is beneficial to improving the electrochemical properties of the secondary battery, such as capacity and cycle performance.

[0033] The third aspect of the present application provides a method for preparing the positive electrode active material described above. According to an embodiment of the present application, the method comprises: x M 1-x (OH) 2 、SiO 2 , the raw material mixture containing the oxide of element A is heated to 450°C to 650°C in a pure oxygen atmosphere, and kept warm for 4h to 8h to obtain a calcined product; the calcined product is heated to 650°C to 800°C in a pure oxygen atmosphere, and kept warm for 10h to 15h to obtain the positive electrode material.

[0034] In some embodiments, the raw material mixture further includes an additive containing element D. Specifically, the additive containing element D may be an oxide of element D, for example, including but not limited to MoO 3 、 2 O 5 , WO 3 , Sb 2 O 3 SnO 2 , Nb 2 O 3 , Nb 2 O 5 At least one of .

[0035] In a fourth aspect of the present application, an electric device is provided. According to an embodiment of the present application, the electric device includes the secondary battery described above. The electric device has all the features and advantages of the secondary battery described above, which will not be described one by one here.

[0036] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0038] Figure 1 This is a schematic structural diagram of a secondary battery according to an embodiment of the present application.

[0039] Figure 2 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application.

[0040] Figure 3 This is a SEM photograph of the positive electrode active material of Example 1 of the present application.

[0041] Figure 4 This is a SEM photograph of the positive electrode active material of Example 4 of the present application.

[0042] Figure 5 This is a SEM photograph of the positive electrode active material of Example 5 of the present application.

[0043] Figure 6 This is the Al element distribution diagram obtained by TEM-EDS testing of the positive electrode active material in Example 1 of the present application.

[0044] Figure 7 This is the Si element distribution diagram obtained by TEM-EDS testing of the positive electrode active material in Example 1 of the present application.

[0045] Figure 8 This is the W element distribution diagram obtained by TEM-EDS testing of the positive electrode active material in Example 1 of the present application.

[0046] The figures are as follows:

[0047] 1: Battery 100: Electrode assembly 200: Housing 300: Cover DETAILED DESCRIPTION

[0048] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0050] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0051] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0052] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0053] In the description of the embodiments of the present application, the term "plurality" means two or more (including two). Similarly, "multiple groups" means two or more groups (including two groups), and "multiple sheets" means two or more sheets (including two sheets).

[0054] Although the high-nickel cathode material has a relatively high energy density, the performance of the high-nickel cathode material is more active, and many new challenges are also faced in applications: for example, as the nickel content increases, the oxygen release of the material causes a decrease in thermal stability; during the cycling process, the attenuation is accelerated due to particle cracking, and the cycling performance of the battery is significantly reduced.

[0055] To address the above problems, the present application proposes doping and modifying the high-nickel cathode material in the secondary battery with Si and element A simultaneously. Among them, doping with Si can significantly improve the cycling performance, but at the same time, it is accompanied by a serious capacity decline. Through research, it is found that doping with element A simultaneously can effectively alleviate the capacity decline caused by doping with Si. When used in a secondary battery, it can improve the cycling performance of the secondary battery while reducing the amplitude of capacity reduction.

[0056] It can be understood that the secondary battery includes but is not limited to lithium-ion batteries; the specific shape of the secondary battery can be square, cylindrical, and other regular or irregular shapes; the outer packaging of the secondary battery can be a hard shell (such as a steel shell, a hard plastic shell, etc.), or a soft shell (such as an aluminum-plastic film, a bag-type soft shell, etc.). And the above secondary battery can exist in the form of a single battery cell or multiple battery cells assembled. And the secondary battery can be used as a power source or an energy storage system for electrical devices such as vehicles, power tools, mobile terminals, and flying devices.

[0057] The secondary battery, the positive active material thereof, its preparation method, and the electrical device of the present application will be described in detail below with reference to the accompanying drawings.

[0058] In one aspect of the present application, the present application provides a secondary battery. According to the embodiments of the present application, the secondary battery includes an outer packaging and an electrode assembly and an electrolyte located inside the outer packaging. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is located between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive active material, and the positive active material includes a compound shown in Formula 1 and a doping element:

[0059] Li 1+a Ni x M 1-x O 2 Formula 1

[0060] where 0 < a < 0.08, 0.8 < x < 1.0, and M includes at least one of Co, Mn, and Al;

[0061] The doping element includes Si and element A, and the element A includes at least one of Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti and La.

[0062] It can be understood that the doping elements Si and element A in this article are doped in the bulk phase of the compound shown in Formula 1, that is, Si and element A enter the crystal lattice of the compound shown in Formula 1; specifically, Si and element A can occupy the transition metal site or lithium site in the compound shown in Formula 1; as an example, Na, Mg, Ca and Zr tend to occupy the Li site, and other elements tend to occupy the transition metal site.

[0063] In the secondary battery according to the embodiment of the present application, Si and element A are simultaneously doped into the positive electrode active material to form high entropy doping in the bulk phase, which can reduce the capacity reduction of the positive electrode material while improving the cycle performance of the secondary battery.

[0064] According to an embodiment of the present application, the Si is uniformly distributed in the compound represented by Formula 1.

[0065] According to an embodiment of the present application, the element A is uniformly distributed in the compound represented by Formula 1.

[0066] It can be understood that the uniform distribution of Si and element A in the compound represented by formula 1 means that three points are randomly selected in the bulk phase of the material, and their doping concentrations are measured as X1, X2 and X3, respectively, and the three meet the following formula:

[0067]

[0068] Wherein, X=(X1+X2+X3) / 3.

[0069] The specific doping concentration can be detected by transmission electron microscope-energy dispersive spectrometer (TEM-EDS).

[0070] Specifically, during the preparation process, the compound of Si and element A can undergo a low eutectic phenomenon to form a molten salt system, which helps Si and element A to be doped into the bulk phase of the positive electrode active material, thereby better playing a role in improving cycle performance and alleviating capacity reduction.

[0071] The melting point of a material is caused by intermolecular forces. The reason why the melting point decreases after mixing multiple substances with different melting points is that the intermolecular forces in the mixture have changed. In pure substances, the intermolecular forces are the same, so the melting point is fixed. However, in a mixture, the intermolecular forces of multiple substances are different, causing the melting point to change. Specifically, when two substances are mixed together, they interact with each other, and this interaction weakens the intermolecular forces, resulting in a lower melting point, which is the eutectic phenomenon.

[0072] According to the embodiments of the present application, the average doping concentration of Si in the compound represented by the formula 1 is 1000ppm to 10000ppm, calculated by mass ratio, such as 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, etc. Within the above doping concentration range, the cycle performance of the positive electrode active material can be well improved.

[0073] According to the embodiments of the present application, the average doping concentration of the element A in the compound represented by the formula 1 is 1000ppm to 10000ppm, calculated by mass ratio, such as 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, etc. Within the above doping concentration range, the reduction in the capacity of the positive electrode active material caused by doping Si can be effectively alleviated.

[0074] It can be understood that the average doping concentration herein refers to the average doping concentration of the doping element in the entire particle of the compound shown in Formula 1. Specifically, it can be detected by an inductively coupled plasma spectrometer. As an example, the positive electrode material particles can be dissolved in a solution such as aqua regia, and then the content of the doping element can be detected by an inductively coupled plasma spectrometer, and the average doping concentration of the doping element can be obtained by calculation.

[0075] According to an embodiment of the present application, the doping element further includes element D, and the element D includes at least one of Mo, Ta, W, Sb, Sn and Nb. Specifically, element D can inhibit grain coarsening, widen the sintering range, help to obtain better crystallinity, release stress during the cycle process, slow down the formation of microcracks, and thus improve the cycle performance of the secondary battery.

[0076] According to an embodiment of the present application, the doping concentration of the element D at the grain boundary is greater than the doping concentration inside the grain.

[0077] It can be understood that a grain boundary is the interface between grains with the same structure but different orientations. On the grain interface, the atomic arrangement transitions from one orientation to another, so the atomic arrangement at the grain boundary is in a transitional state; the contact interface between grains is called a grain boundary. Specifically, the grain boundary can be observed by an electron backscatter diffractometer.

[0078] Specifically, the element D segregates and is enriched at the grain boundaries, which can further inhibit grain coarsening, widen the sintering range, obtain better crystallinity, and increase the porosity of the material, which is conducive to releasing stress and slowing down the formation of microcracks during the cycle. In addition, it can be used as a Li lithium conductor to increase capacity; and as a grain boundary level coating layer, it can effectively inhibit electrolyte side reactions and improve the cycle performance of secondary batteries.

[0079] According to the embodiments of the present application, the average doping concentration of the element D in the compound represented by the formula 1 is 500ppm to 5000ppm, calculated by mass ratio, such as 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, etc. Within the above doping concentration range, the effects of grain refinement, widening sintering temperature, and slowing down microcrack formation are further improved.

[0080] According to an embodiment of the present application, the Li / Ni mixing degree of the positive electrode active material is 2.5% to 6%, specifically 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, etc. Within the above-mentioned Li / Ni mixing degree range, high entropy doping and lattice stabilization can be achieved, while the Li / Ni mixing degree is relatively low, which is beneficial to improving the electrochemical properties of the secondary battery, such as capacity and cycle performance.

[0081] It is understandable that in high nickel positive electrode materials, Ni 2+ The ionic radius and Li + The ionic radius of Ni is very close, which makes Ni, which should have stayed in the transition metal layer, 2+ Some of them will migrate to the Li layer and occupy the Li + The spatial position of Ni is called Li / Ni mixing. The degree of Li / Ni mixing refers to the 2+ Occupy Li + The ratio of the spatial points can be detected by referring to the conventional technology in the field. As an example, it can be obtained by fine-tuning the XRD spectrum of the high-nickel positive electrode material.

[0082] In some embodiments, the positive electrode sheet of the secondary battery may include a positive electrode current collector and a positive electrode film layer located on at least one surface of the positive electrode current collector. As an example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0083] According to an embodiment of the present application, the positive electrode film layer may include the positive electrode active material, a conductive agent, a binder, and optionally a functional additive.

[0084] In some embodiments, in addition to the positive electrode active materials described above, the positive electrode film layer may also contain other positive electrode active materials. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other materials that can be used as positive electrode active materials for secondary batteries may also be used. Examples of lithium transition metal oxides may include, but are not limited to, lithium nickel oxides (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide and modified compounds thereof. Examples of lithium phosphates containing olivine structures may include but are not limited to lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0085] In some embodiments, the binder in the positive electrode film layer may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0086] In some embodiments, the conductive agent in the positive electrode film layer may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0087] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0088] According to an embodiment of the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0089] In some embodiments, in addition to the positive electrode sheet, the secondary battery may further include a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, an electrolyte that soaks the positive electrode sheet, the negative electrode sheet and the separator, and an outer package.

[0090] According to an embodiment of the present application, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0091] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0092] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include one or more of graphite, soft carbon, hard carbon, mesophase carbon microspheres, carbon fibers, carbon nanotubes, elemental silicon, silicon oxides, silicon carbon composites, and lithium titanate. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0093] In some embodiments, the negative electrode film layer may further include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0094] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0095] In some embodiments, the negative electrode film layer may also optionally include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), a lithium supplement, a flame retardant additive, a film-forming additive, a thermal stability additive, and the like.

[0096] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0097] The present application has no particular restrictions on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. As an example, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular restrictions. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular restrictions.

[0098] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0099] According to an embodiment of the present application, the electrolyte may include an electrolyte lithium salt, an organic solvent, and optional additives.

[0100] According to the embodiments of the present application, the type of electrolyte lithium salt is not particularly limited and can be selected according to actual needs. Specifically, the electrolyte lithium salt can be selected from LiN(C x1 F 2x1+1 SO 2 )(C y1 F 2y1+1 SO 2 )、LiPF 6 , LiBF 4 、LiBOB、LiAsF6 、Li(FSO 2 ) 2 N、LiCF 3 SO 3 and LiClO 4 One or more of, wherein x1 and y1 are natural numbers. In the electrolyte, the concentration of the lithium salt may range from 0.5M to 2.5M, specifically 0.8M to 2M, such as 0.5M, 0.6M, 0.7M, 0.8M, 0.9M, 1.0M, 1.2M, 1.5M, 1.8M, 2.0M, 2.2M, 2.5M, etc.

[0101] According to an embodiment of the present application, the type of the organic solvent is not particularly limited and can be selected according to actual needs. Specifically, the organic solvent may include one or more of linear carbonates, cyclic carbonates, and carboxylates. Among them, the types of linear carbonates, cyclic carbonates, and carboxylates are not specifically limited and can be selected according to actual needs. As an example, the organic solvent may include one or more of diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, γ-butyrolactone, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl propionate, and tetrahydrofuran.

[0102] In some embodiments, the electrolyte may contain at least one additive selected from the group consisting of monofluoro lithium phosphate, difluoro lithium phosphate, and fluorosulfonate.

[0103] The above fluorosulfonate is (FSO 3 ) y3 M 2 y3+ , M 2 y3+ is a metal ion or an organic cation; the metal ion comprises Li + , Na + , K + , Rb + , Cs + ,Mg 2+ , Ca 2+ , Ba 2+ , Al 3+ , Fe 2+ , Cu 2+ , Fe 3+ , Ni 2+ , Ni 3+One or more of the above. Based on the total mass of the electrolyte, the mass percentage of the fluorosulfonate additive can be W1, where 0.01% ≤ W1 ≤ 20%, specifically 0.1% ≤ W1 ≤ 10%, and more specifically 0.3% ≤ W1 ≤ 5%.

[0104] According to an embodiment of the present application, the electrolyte may further include other additives, such as at least one of a cyclic carbonate compound containing an unsaturated bond, a halogen-substituted cyclic carbonate compound, a sulfate compound, a sulfite compound, a sultone compound, a disulfonic acid compound, a nitrile compound, an aromatic compound, an isocyanate compound, a phosphazene compound, a cyclic anhydride compound, a phosphite compound, a phosphate compound, a borate compound, and a carboxylate compound.

[0105] In some embodiments, the outer package can be used to encapsulate the above electrode assembly and electrolyte. In some embodiments, the outer package of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery can also be a soft package, such as a pouch soft package. The material of the soft package can be plastic. As plastics, polypropylene, polybutylene terephthalate, and polybutylene succinate can be enumerated.

[0106] The present application does not particularly limit the shape of the secondary battery, which can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 is a secondary battery 1 with a square structure as an example. Refer to Figure 1 , the outer package may include a housing 200 and a cover plate 300. Among them, the housing 200 may include a bottom plate and side plates connected to the bottom plate, and the bottom plate and the side plates enclose a receiving cavity. The housing 200 has an opening communicating with the receiving cavity, and the cover plate 300 can be covered on the opening to close the receiving cavity. The above electrode assembly 100 of the present application is encapsulated in the receiving cavity. The electrolyte infiltrates into the electrode assembly 100. The number of electrode assemblies 100 contained in the battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.

[0107] In a second aspect of the present application, a positive electrode active material is provided. According to an embodiment of the present application, the positive electrode active material includes a compound shown in Formula 1 and a doping element:

[0108] Li 1+a Ni x M 1-x O 2 Formula 1

[0109] where 0 < a < 0.08, 0.8 < x < 1.0, and M includes at least one of Co, Mn, and Al;

[0110] The doping element includes Si and element A, and the element A includes at least one of Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti and La.

[0111] In the positive electrode active material, the cycle performance of the secondary battery using the positive electrode active material can be improved by doping Si, and the capacity reduction caused by doping Si can be reduced by doping element A. The secondary battery using the positive electrode active material has good cycle performance and high capacity.

[0112] According to an embodiment of the present application, the element A includes at least one of Sr, B, and Al. Thus, Si is more easily doped into the bulk phase of the compound shown in Formula 1, the structural stability can be further improved, and the capacity of the positive electrode active material is reduced to a lesser extent.

[0113] According to an embodiment of the present application, the Si is uniformly distributed in the compound represented by Formula 1.

[0114] According to an embodiment of the present application, the element A is uniformly distributed in the compound represented by Formula 1.

[0115] Specifically, during the preparation process, the compound of Si and element A can undergo a low eutectic phenomenon to form a molten salt system, which helps Si and element A to be doped into the bulk phase of the positive electrode active material and evenly distributed, thereby better playing a role in improving cycle performance and alleviating capacity reduction.

[0116] According to the embodiments of the present application, the average doping concentration of Si in the compound represented by the formula 1 is 1000ppm to 10000ppm, calculated by mass ratio, such as 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, etc. Within the above doping concentration range, the cycle performance of the positive electrode active material can be well improved.

[0117] According to the embodiments of the present application, calculated by mass ratio, the average doping concentration of the element A in the compound represented by the formula 1 is 1000ppm to 10000ppm, specifically 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, etc. Within the above doping concentration range, the capacity reduction caused by doping Si element can be effectively alleviated.

[0118] According to an embodiment of the present application, the doping element further includes element D, and the element D includes at least one of Mo, Ta, W, Sb, Sn and Nb. In some specific examples, element D includes W. Specifically, element D can inhibit grain coarsening, widen the sintering range, help to obtain better crystallinity, release stress during the cycle process, slow down the formation of microcracks, and thus improve the cycle performance of the secondary battery.

[0119] According to the embodiments of the present application, the doping concentration of the element D at the grain boundary is greater than the doping concentration inside the grain. Specifically, the element D segregates and enriches at the grain boundary, which can further inhibit grain coarsening, widen the sintering range, obtain better crystallinity, increase the material porosity, and facilitate stress release and slow down microcrack formation during the cycle. In addition, it can be used as a Li lithium conductor to increase capacity; and as a grain boundary layer coating, it can effectively inhibit electrolyte side reactions and improve the cycle performance of secondary batteries.

[0120] According to the embodiments of the present application, the average doping concentration of the element D in the compound represented by the formula 1 is 500ppm to 5000ppm, calculated by mass ratio, such as 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, etc. Within the above doping concentration range, the effects of grain refinement, widening sintering temperature, and slowing down microcrack formation are further improved.

[0121] According to the embodiments of the present application, the Li / Ni mixing degree of the positive electrode active material is 2.5% to 6%, and in some embodiments, it can be 3% to 4.3%, specifically 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, etc. Within the above-mentioned Li / Ni mixing degree range, high entropy doping and lattice stabilization can be achieved, and at the same time, the Li / Ni mixing degree is relatively low, which is conducive to improving the electrochemical properties such as capacity and cycle performance of the secondary battery.

[0122] It can be understood that the positive electrode active material according to the embodiment of the present application can be a polycrystalline material, a single crystal material, or a mixture of a single crystal material and a polycrystalline material, and can be flexibly selected according to actual needs. In some embodiments, the positive electrode active material is a polycrystalline material; when the positive electrode active material is a polycrystalline material, its primary grains are fine, which is conducive to lithium ion deintercalation, and the secondary particles have a high porosity, which is conducive to stress release, so that while having good lithium ion transmission performance, it is not easy to produce microcracks, which can effectively improve the cycle performance of the secondary battery and extend its service life.

[0123] The third aspect of the present application provides a method for preparing the positive electrode active material described above. According to an embodiment of the present application, the method comprises: x M 1-x (OH) 2 、SiO 2 , a raw material mixture containing an oxide of element A is heated to 450° C. to 650° C. (specifically, 450° C., 475° C., 500° C., 525° C., 550° C., 575° C., 600° C., 625° C., 650° C., etc.) in a pure oxygen atmosphere, and kept warm for 4 h to 8 h (specifically, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, etc.) to obtain a calcined product; The calcined product is heated to 650°C ~ 800°C (specifically 650°C, 675°C, 700°C, 725°C, 750°C, 775°C, 800°C, etc.) in a pure oxygen atmosphere and kept warm for 10h ~ 15h (specifically 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, etc.) to obtain the positive electrode material.

[0124] In some embodiments, lithium salt, Ni x M 1-x (OH) 2 、SiO 2 , and the oxide containing element A are pre-mixed to obtain a raw material mixture, and then the raw material mixture is placed in a heating device for heat treatment; lithium salt, Ni x M 1-x (OH) 2 、SiO 2 , oxides containing element A are added to the heating equipment for heat treatment. x M 1-x (OH) 2 、SiO 2 , the amount of the oxide containing element A is such that the compound represented by formula 1 described above and the doping element within the above-mentioned doping concentration range can be obtained.

[0125] In some embodiments, the specific types of lithium salt and oxide of element A are not particularly limited and can be flexibly selected according to actual conditions. As an example, lithium salt includes but is not limited to LiOH, LiOH·H 2 O and Li 2 CO 3 ; Oxides of element A include but are not limited to B 2 O 3 、SrO、BaO、Al 2 O 3 , CaO, CeO 2 , K 2 O, MgO, ZrO 2 、TiO 2 ,La 2 O 3 At least one of .

[0126] In some embodiments, the raw material mixture further includes an additive containing element D. Specifically, the additive containing element D may be an oxide of element D, for example, including but not limited to MoO 3 、 2 O 5 , WO 3 , Sb 2 O 3 SnO 2 , Nb 2 O 3 , Nb 2 O 5 At least one of .

[0127] In some embodiments, before the second calcination, the first calcined product may be crushed in advance to eliminate agglomeration during the sintering process and obtain a first calcined product of target particle size. The crushing treatment methods that can be used include but are not limited to mechanical crushing, air flow milling, etc.; and the specific target particle size can be flexibly selected and adjusted according to actual needs, and this application does not impose any special restrictions.

[0128] In some specific embodiments, the positive electrode active material can be prepared by the following steps: Ni x M 1-x (OH) 2 , lithium salt, SiO 2 and the oxide of element A are mixed evenly, and then the mixed raw material mixture powder is added to the corundum porcelain boat, placed in a tube furnace, pure oxygen is introduced, the temperature is raised to 450°C to 650°C, and after keeping the temperature for 4h to 8h, the temperature is lowered to room temperature. The cooled powder is taken out, mechanically crushed, and then added to the corundum porcelain boat again, placed in a tube furnace, pure oxygen is introduced, the temperature is raised to 650°C to 800°C, and after keeping the temperature for 10h to 15h, the temperature is lowered to room temperature to obtain the positive electrode active material.

[0129] The third aspect of the present application provides an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described above. The electric device has all the features and advantages of the secondary battery described above, which will not be described one by one here.

[0130] According to an embodiment of the present application, the secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0131] Figure 2 The power consumption device is taken as an example, and the power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.

[0132] The present invention will be further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0133] Embodiment 1:

[0134] Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 、LiOH·H 2 O(precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 With lithium salt LiOH·H 2 O has a molar ratio of 1:1.05), SiO 2 (average doping concentration is 1000ppm), B 2 O 3 (average doping concentration is 2000ppm), SrO (average doping concentration is 3000ppm), Al 2 O 3 (average doping concentration is 500ppm), WO 3 (The average doping concentration is 2000ppm) mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2 L / min, increase the temperature to 550°C at a rate of 5°C / min, keep warm at 550°C for 5 hours, and then cool down to room temperature at a rate of 5°C / min.

[0135] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After being kept at 780°C for 12 hours, the temperature was lowered to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Example 1.

[0136] Embodiment 2:

[0137] Will Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 、LiOH·H 2 O(precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 With lithium salt LiOH·H 2 O has a molar ratio of 1:1.05), SiO 2 (average doping concentration is 1000ppm), B 2 O 3 (average doping concentration is 2000ppm), SrO (average doping concentration is 3000ppm), Al 2 O 3 (the average doping concentration is 500ppm), mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2L / min, increase the temperature to 550°C at a rate of 5°C / min, keep warm at 550°C for 5 hours, and then cool down to room temperature at a rate of 5°C / min.

[0138] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After keeping at 780°C for 12 hours, the temperature was lowered to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Example 2.

[0139] Embodiment 3:

[0140] Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 、LiOH·H 2 O(precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 With lithium salt LiOH·H 2 O has a molar ratio of 1:1.05), SiO 2(average doping concentration is 1000ppm), B 2 O 3 (average doping concentration is 2000ppm), SrO (average doping concentration is 3000ppm), WO 3 (The average doping concentration is 2000ppm) mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2 L / min, increase the temperature to 550°C at a rate of 5°C / min, keep warm at 550°C for 5 hours, and then cool down to room temperature at a rate of 5°C / min.

[0141] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After being kept at 780°C for 12 hours, the temperature was lowered to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Example 3.

[0142] Example 4

[0143] Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 、LiOH·H 2 O(precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 With lithium salt LiOH·H 2 O has a molar ratio of 1:1.05), SiO 2 (average doping concentration is 1000ppm), B 2 O 3 (average doping concentration is 3000ppm), SrO (average doping concentration is 2000ppm), Al 2 O 3 (average doping concentration is 500ppm), WO 3 (The average doping concentration is 2000ppm) mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2 L / min, increase the temperature to 550°C at a rate of 5°C / min, keep it at 450°C for 5 hours, and then cool it to room temperature at a rate of 5°C / min.

[0144] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After keeping at 780°C for 12 hours, the temperature was lowered to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Example 4.

[0145] Example 5

[0146] Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 、LiOH·H 2 O(precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 With lithium salt LiOH·H 2 O has a molar ratio of 1:1.05), SiO 2 (average doping concentration is 3000ppm), B 2 O 3 (average doping concentration is 2000ppm), SrO (average doping concentration is 1000ppm), Al 2 O 3 (average doping concentration is 500ppm), WO 3 (The average doping concentration is 2000ppm) mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2 L / min, increase the temperature to 550°C at a rate of 5°C / min, keep it at 650°C for 5 hours, and then cool it to room temperature at a rate of 5°C / min.

[0147] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After keeping at 780°C for 12 hours, the temperature was lowered to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Example 5.

[0148] Example 6

[0149] Ni 0.95 Co 0.04 Mn 0.01 (OH) 2 、LiOH·H 2 O(precursor Ni 0.95 Co 0.04 Mn 0.01 (OH) 2 With lithium salt LiOH·H 2 O has a molar ratio of 1:1.05), SiO 2 (average doping concentration is 1000ppm), B 2 O 3 (average doping concentration is 2000ppm), SrO (average doping concentration is 3000ppm), Al 2 O 3(average doping concentration is 500ppm), WO 3 (The average doping concentration is 2000ppm) mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2 L / min, increase the temperature to 550°C at a rate of 5°C / min, keep warm at 550°C for 5 hours, and then cool down to room temperature at a rate of 5°C / min.

[0150] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After being kept at 780°C for 12 hours, the temperature was lowered to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Example 6.

[0151] Comparative Example 1:

[0152] Will Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 、LiOH·H 2 O(precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 With lithium salt LiOH·H 2 The molar ratio of O is 1:1.05), B 2 O 3 (average doping concentration is 2000ppm), SrO (average doping concentration is 3000ppm), Al 2 O 3 (average doping concentration is 500ppm), WO 3 (The average doping concentration is 2000ppm) mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2 L / min, increase the temperature to 550°C at a rate of 5°C / min, keep warm at 550°C for 5 hours, and then cool down to room temperature at a rate of 5°C / min.

[0153] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After being kept at 780°C for 12 hours, the temperature was cooled to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Comparative Example 1.

[0154] Comparative Example 2

[0155] Ni 0.83 Co 0.12 Mn 0.05 (OH)2 、LiOH·H 2 O(precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 With lithium salt LiOH·H 2 O has a molar ratio of 1:1.05), SiO 2 (the average doping concentration is 1000ppm) mix evenly, then add the mixed powder into a corundum porcelain boat, put it into a tubular furnace, introduce pure oxygen at a flow rate of 0.2L / min, increase the temperature to 550℃ at a rate of 5℃ / min, keep warm at 550℃ for 5 hours, and then cool down to room temperature at a rate of 5℃ / min.

[0156] The cooled powder was taken out, mechanically crushed and added into the corundum porcelain boat again, put into a tubular furnace, and pure oxygen was introduced at a flow rate of 0.2 L / min. The temperature was raised to 780°C at a heating rate of 5°C / min. After keeping at 780°C for 12 hours, the temperature was cooled to room temperature at a cooling rate of 5°C / min to obtain the positive electrode active material product of Comparative Example 2.

[0157] Performance Testing

[0158] 1. Preparation of button cells:

[0159] The positive electrode active material, polyvinylidene fluoride (PVDF) and conductive carbon prepared in the above embodiment or comparative example are added to a certain amount of N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and stirred in a drying room to form a slurry. The slurry is coated on an aluminum foil, dried, and cold-pressed to form a positive electrode sheet. A lithium sheet is used as a negative electrode. The electrolyte is composed of a lithium salt and a solvent. The lithium salt is 1 mol / L LiPF 6 The solvent is EC+DEC+DMC in a volume ratio of 1:1:1, and the button batteries (referred to as button batteries) are assembled in a button battery box.

[0160] 2. Test method for initial gram capacity after power-off:

[0161] At 2.8-4.3V, charge to 4.3V at 0.1C, then charge at constant voltage at 4.3V to a current ≤ 0.05mA, let stand for 2min, the charge capacity at this time is recorded as C0, then discharge to 2.8V at 0.1C, the discharge capacity at this time is the initial gram capacity, recorded as D0.

[0162] 3. Preparation of full battery:

[0163] The positive electrode active material prepared in the above embodiment or comparative example is fully stirred and mixed with the conductive agent acetylene black and the binder PVDF in an N-methylpyrrolidone solvent system in a weight ratio of 94:3:3, and then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode plate. The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carbon methyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on a copper foil, dried, and cold pressed to obtain a negative electrode plate. A polyethylene (PE) porous polymer film is used as an isolation membrane. The positive electrode plate, isolation membrane, and negative electrode plate are stacked in order so that the isolation membrane is located between the positive and negative electrodes to play an isolation role, and then wound to obtain a bare battery cell. The bare battery cell is placed in an outer package, and an electrolyte (composed of a lithium salt and a solvent, with the lithium salt being 1 mol / L LiPF 6 , the solvent is EC+DEC+DMC with a volume ratio of 1:1:1) and encapsulated to obtain a full battery.

[0164] 4. Full battery 45℃ cycle performance test:

[0165] Under a constant temperature environment of 45°C, charge to 4.25V at 1C at 2.8-4.25V, then charge at constant voltage at 4.25V to a current ≤ 0.05mA, let stand for 5min, and then discharge to 2.8V at 1C. The capacity is recorded as Dn (n=0, 1, 2...), repeat the previous process, and record the cycle retention rate after 300 cycles (i.e. D300 / C0×100%).

[0166] 5. Li / Ni mixing degree test

[0167] By refining the X-ray diffraction pattern of the positive electrode active material, the position distribution of Ni and Li is determined, and then their occupancy in the crystal lattice is determined, that is, the Li / Ni mixed arrangement.

[0168] Among them, the XRD test conditions are:

[0169] 1. Sample preparation:

[0170] Positive electrode powder: 1mm deep, 25mm diameter sample slot flat sample preparation method

[0171] 2. Test:

[0172] Positive pole: starting angle 15°, ending angle 70°, step length 0.01671°, each step duration 0.24s

[0173] 3. Fixed core parameters:

[0174] Voltage: 40KV, Current: 40mA, Anti-scatter slit: 1mm, 2Theta angle: 10-80°, Scan speed: 2° / min.

[0175] 6. Doping concentration test:

[0176] TEM-EDS is used to perform element mapping or line scanning to obtain the element doping concentration at different locations.

[0177] FIB (focused ion beam technology) is used for sample preparation. The main steps include:

[0178] Pretreatment: The goal is to make the IC sample to be analyzed and cut into pieces of the same size and bonded together. The key to this process is to use an adhesive that can be dissolved in organic solvents and use a "splitting" sample preparation technique to thin the IC sample to 20-30μm. The target to be analyzed should fall in the center of the sample.

[0179] Marking: A liquid gallium metal source is used at the top of the ion chamber to extract positively charged gallium ions through a strong electric field, accelerating the high-energy ion beam to impact the sputtered sample to achieve thinning. Before thinning, a 1μm to 2μm thick Pt film is deposited at the target position to protect the target area of ​​the sample.

[0180] Thinning stage: Use the Box sputtering mode to thin the sample on both sides with equal thickness starting from 20μm, and the thinning depth is 3.5μm. The thinning selection box of the ion beam can be defined at a position of 5μm to 2μm from the sample target. The ion beam intensity decreases from 6nA to 3nA. When the sample is thinned to 1 to 2μm from the target, it enters the precision thinning area and uses a 1nA intensity ion beam. During the thinning process, the monitor continuously monitors the thinning process until the TEM observation requirements are met and the sample to be tested is obtained.

[0181] Then, the sample to be tested is subjected to TEM observation and element mapping or line scanning to obtain the doping concentration of different elements. The element distribution diagrams of aluminum, silicon and tungsten in the positive electrode active material in Example 1 are shown in FIG.

[0182] 6. Figure 7 and Figure 8 ,It can be seen intuitively from the element distribution diagram that aluminum ,silicon elements are evenly distributed in the positive electrode active ,material, and tungsten elements are obviously enriched at the grain boundaries.

[0183] 7. IPC test:

[0184] The positive electrode active material was dissolved in a mixed solvent (nitric acid and hydrochloric acid were mixed in a volume ratio of 1:1). For example, 0.4 g of the positive electrode active material was diluted with 10 mL of the mixed solvent and the volume was fixed to 100 mL. The obtained solution was then measured for the average doping concentration of each metal element by ICP-OES, Thermo ICAP7400, with reference to US EPA 6010D-2014 inductively coupled plasma atomic emission spectrometry, in units of ppm.

[0185] 8. SEM observation

[0186] Sample preparation: Evenly apply a small amount of positive electrode active material powder on the conductive carbon glue. The morphology of the positive electrode active material particles was tested using a Navigator-100 high-throughput scanning electron microscope (SEM) from Focal Beam Technology. The SEM test conditions were: mode: BSE (backscatter detector), voltage: 3KV, working distance: 5mm. The SEM photos of the positive electrode active materials in Example 1, Example 4 and Example 5 are shown in Figure 10 and Figure 11, respectively. Figure 3 , Figure 4 and Figure 5 .

[0187] Table 1: Characterization of cathode active materials

[0188] Li / Ni mixing degree / % Example 1 4 Example 2 3.7 Example 3 3 Example 4 3.9 Example 5 3.8 Example 6 4.3 Comparative Example 1 2.7 Comparative Example 2 1.2

[0189] Table 2: Battery performance test results

[0190]

[0191]

[0192] Table 3: Test results of element doping concentration at different sites of positive electrode active material in Example 1

[0193]

[0194] Note: In Table 3, X1, X2, and X3 are located at 0nm, 30nm, and 60nm away from the grain boundary, respectively.

[0195] It can be seen from the above test data that the secondary battery of the present application has better cycle performance and a smaller capacity reduction by simultaneously doping Si element and A element in the positive electrode active material.

[0196] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A secondary battery, characterized in that: It includes an outer package, an electrode assembly and an electrolyte located inside the outer package. The electrode assembly includes a positive electrode plate, a negative electrode plate and a separator. The separator is located between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode active material, and the positive electrode active material includes a compound shown in Formula 1 and a doping element: Li 1+a Ni x M 1-x O2 type 1 Wherein, 0 < a < 0.08, 0.8 < x < 1.0, and M includes at least one of Co, Mn, and Al; The doping element includes Si and element A, and element A includes at least one of Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti, and La.

2. The secondary battery according to claim 1, characterized in that: The Si is uniformly distributed in the compound shown in Formula 1.

3. The secondary battery according to claim 1 or 2, characterized in that: The element A is uniformly distributed in the compound shown in Formula 1.

4. The secondary battery according to any one of claims 1 to 3, characterized in that Calculated by mass ratio, the average doping concentration of Si in the compound shown in Formula 1 is 1000 ppm to 10000 ppm; and / or Calculated by mass ratio, the average doping concentration of the element A in the compound shown in Formula 1 is 1000 ppm to 10000 ppm.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The doping element further includes element D, and element D includes at least one of Mo, Ta, W, Sb, Sn, and Nb.

6. The secondary battery according to claim 5, characterized in that: The doping concentration of the element D at the grain boundary is greater than that in the grain interior.

7. The secondary battery according to claim 5 or 6, characterized in that: Calculated by mass ratio, the average doping concentration of the element D in the compound shown in Formula 1 is 500 ppm to 5000 ppm.

8. The secondary battery according to any one of claims 1 to 7, characterized in that The Li / Ni mixing degree of the positive electrode active material is 2.5% to 6%.

9. A positive electrode active material, characterized in that: It includes a compound shown in Formula 1 and a doping element: Li 1+a Ni x M 1-x O2 type 1 Wherein, 0 < a < 0.08, 0.8 < x < 1.0, and M includes at least one of Co, Mn, and Al; The doping element includes Si and element A, and element A includes at least one of Sr, B, Ba, Al, Ca, Ge, K, Mg, Zr, Ti, and La.

10. The positive electrode active material according to claim 9, characterized in that The Si is uniformly distributed in the compound shown in Formula 1.

11. The positive electrode active material according to claim 9 or 10, characterized in that: The element A is uniformly distributed in the compound shown in Formula 1.

12. The positive electrode active material according to claim 10 or 11, characterized in that: Calculated by mass ratio, the average doping concentration of Si in the compound shown in Formula 1 is 1000 ppm to 10000 ppm; and / or Calculated by mass ratio, the average doping concentration of the element A in the compound shown in Formula 1 is 1000 ppm to 10000 ppm.

13. The positive electrode active material according to any one of claims 9 to 12, characterized in that: The doping element further includes element D, and element D includes at least one of Mo, Ta, W, Sb, Sn, and Nb.

14. The positive electrode active material according to claim 13, characterized in that The doping concentration of the element D at the grain boundary is greater than that in the grain interior.

15. The positive electrode active material according to claim 13 or 14, characterized in that: Calculated by mass ratio, the average doping concentration of the element D in the compound shown in Formula 1 is 500 ppm to 5000 ppm.

16. The positive electrode active material according to any one of claims 9 to 15, characterized in that The Li / Ni mixing degree of the positive electrode active material is 2.5% to 6%.

17. A method for preparing the positive electrode active material according to any one of claims 9 to 16, characterized in that: It includes: Will include lithium salts, Ni x M 1-x The raw material mixture of (OH)2, SiO2 and oxide containing element A is heated to 450°C to 650°C in a pure oxygen atmosphere and kept at this temperature for 4h to 8h to obtain a calcined product; Heating the first-fired product in a pure oxygen atmosphere to 650°C to 800°C and holding for 10 h to 15 h to obtain the positive electrode material.

18. The method according to claim 17, characterized in that The raw material mixture further includes an additive containing element D.

19. The method according to claim 18, characterized in that The lithium salt includes at least one of LiOH, LiOH·H2O, and Li2CO3; and / or The oxide containing element A includes at least one of B2O3, SrO, BaO, Al2O3, CaO, CeO2, K2O, MgO, ZrO2, TiO2, and La2O3; and / or The additive containing element D includes at least one of MoO3, Ta2O5, WO3, Sb2O3, SnO2, Nb2O3, and Nb2O5.

20. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Positive electrode active material and positive electrode and rechargeable lithium battery including the positive electrode

    CN101908626A

  • Doped modified NCM cathode material, preparation method thereof, lithium ion battery and electric device

    CN110474035A

  • Cathode active material for lithium secondary battery, method for manufacturing same, cathode comprising same for lithium secondary battery, and lithium secondary battery

    CN111902978A

  • Monocrystal ternary positive electrode material as well as preparation method and application thereof

    CN114243014A

  • Doped and modified ternary material and preparation method thereof

    CN115385398A

Cited By

  • Secondary battery, positive electrode active material, preparation method therefor, and electrical device

    WO2026040494A1